New species of Rhinoleucophenga, a potential predator of pineapple mealybugs - Culik, Mark Paul; Ventura, José Aires (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to describe a new species of Rhinoleucophenga (Diptera: Drosophilidae). Rhinoleucophenga capixabensis sp. nov. is described based on specimens collected from pineapple (Ananas comosus var. comosus) infested with Dysmicoccus brevipes (Hemiptera: Pseudococcidae) in the state of Espírito Santo, Brazil. Distinguishing characters of R. capixabensis sp. nov. include hyaline wings, a strong seta on the second antennal segment, body length of about 2–3 mm, uniformly dark brown scutellum, one pair of strong prescutellar setae, ventral epandrial lobes with about 17–18 teeth, and female cerci with approximately 20 long setae.